Les communistes espagnols : les années difficiles (1947-1956) - Serge Buj (Cahiers de Civilisation Espagnole Contemporaine)
Through documents pertaining to the underground years of the Communist Party of Spain (Partido Comunista de España, pce), particularly reports written in connection with meetings of activists, congresses or conferences, we’ll attempt to understand the image that the pce wanted to project - an image of strength, organization, progress and action. The party’s effort to construct and project an image of itself was motivated by a vital concern: to exist and reinvent itself. At the time of its founding, the pce had very few activists; it became a mass membership party under the exceptional circumstances of the Civil War. The party grew into a militarized organization, with very limited political experience and without a long history. The construction of a democratic party did not begin until the very end of the 1960s. Meanwhile, the party underwent the ordeal of surviving its underground status and an intense repression. Its most dangerous enemy, however, was the passing of time, which was eroding members’ enthusiasm.